An agenda for climate change and mental health in the Philippines - Guinto, Renzo R *; Alejandre, Julius Cesar P; Bongcac, Marianne K; Guilaran, Johnrev; Salcedo, Sena S; Sunglao, Jun Angelo (Elsevier, 2021)
The latest report1 from Climate Cares, based at the Imperial College London, is a welcome addition to the small but slowly growing body of knowledge on the interconnections between climate change and mental health.1 The report identified the different direct and indirect causal pathways, synthesised evidence on current epidemiology and health-system responses from diverse countries, and laid out recommendations for future research, policy, and practice. The report's launch is timely and relevant as the climate crisis intersects with the COVID-19 pandemic, which is also generating a global mental health pandemic.